Using lessons learnt from key stakeholders to increase support for scaling the Reach Up Early Childhood Parenting program - Coore-Hall, Jacqueline; Smith, Joanne; Kelly, Melissa; Baker-Henningham, Helen; Chang, Susan; Walker, Susan (Frontiers in Public Health, 2023)
Sustainable implementation of early childhood programs requires comprehensive resources and materials that are adaptable, scalable and feasible for delivery through multiple sectors. Developers of these programs may need to consider whether additional or modified program resources are required to meet emerging needs, for example as programs go to scale. An active and effective monitoring, evaluation and learning (MEL) process may enable programs to be responsive to demands. This paper reports on how data collected from in depth interviews with key informants and structured small group discussions at a Knowledge Exchange meeting of global partners, drove modifications to the materials, resources and process of the Reach Up: Early Childhood Parenting program.). The program is based on the Jamaica Home Visiting (JHV) model developed in the 1970s, designed primarily for disadvantaged children under 4 years of age in low- and middle-income countries to promote their development through playful caregiver interactions. The curriculum, training manuals and other materials and resources support implementers in the adaptation of the intervention, implementation, workforce training, monitoring and evaluation. The main findings from the thematic analysis of the interview transcripts and meeting notes were the need for (i) advocacy and communication resources and materials to aid prospective implementers and other stakeholders, to make decisions for implementation, ii) revisions and/or additions to the content and formatting of the curriculum, and additional content in the training and other supporting manuals and (iii) enhancements to the training process. This feedback informed the development of new knowledge materials, resources and processes and modifications to existing program materials and resources which will help to support advocacy, ongoing implementations and the process of transitioning to scale.